Analisis Penggunaan QRIS (Quick Response Indonesian Standard) Dengan Pendekatan Technology Acceptance Model (TAM) - Rahimi, Yusnila; Restuti, Sri; Wasnury, Rendra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
QRIS (Quick Response Code Indonesian Standard) is a combination of various types of QR from various Payment System Service Providers (PJSP) that are used to make non-cash payments via QR-Code. The research objective is to explain the effect of perceived usefulness, perceived ease of use on behavioral intention and actual system use which is part of the Technology Acceptance Model (TAM). This type of research is quantitative and carried out using the non-probability sampling method by giving questionnaires to 112 MSME culinary respondents in Pekanbaru City. The data analysis method used in this study is SEM-PLS (Structural Equation Model - Partial Least Squares). The results of this study indicate that perceived usefulness has a positive and significant effect on actual system use, perceived usefulness has a positive and significant effect on behavioral intention, Perceived Ease of Use has a positive and significant effect on perceived usefulness, Perceived Ease of Use has a positive and significant effect actual system use, Perceived Ease of Use has a positive and significant effect on behavioral intention, behavioral intention has a positive and significant effect actual system use. Abstrak QRIS (Quick Response Code Indonesian Standard) adalah penggabungan berbagai macam QR dari berbagai Penyelenggara Jasa Sistem Pembayaran (PJSP) yang digunakan untuk melakukan pembayaran non-tunai melalui QR-Code. Tujuan penelitian adalah untuk menjelaskan pengaruh perceived usefulness, perceived ease of use terhadap behavioral intention dan actual system use yang merupakan bagian dari Technology Acceptance Model (TAM). Jenis penelitian ini adalah kuantitatif dilakukan dengan metode Nonprobability sampling dengan cara memberikan kuesioner kepada 112 responden UMKM kuliner di Kota Pekanbaru. Metode analisis data yang digunakan dalam penelitian ini adalah menggunakan SEM-PLS (Structural Equation Model - Partial Least Squares). Hasil penelitian ini menunjukkan bahwa perceived usefulness berpengaruh positif dan signifikan terhadap actual system use, perceived usefulness berpengaruh positif dan signifikan terhadap behavioral intention, perceived ease of use berpengaruh positif dan signifikan terhadap perceived usefulness, perceived ease of use berpengaruh positif dan signifikan terhadap actual system use, perceived ease of use berpengaruh positif dan signifikan terhadap behavioral intention, behavioral intention berpengaruh positif dan signifikan terhadap actual system use.